Improving of pelB-Secreted MPT64 protein released by Escherichia coli BL21 (DE3) using Triton X-100 and Tween-80 - Kusuma, Sri Agung Fitri; Subroto, Toto; Parwati, Ida; Rukayadi, Yaya; Fadhlillah, Muhammad; Pardede, Ruth Michellee (Wolters Kluwer Medknow Publications, 2022)
pelB has been known as a successful signal peptide to translocate the protein target extracellularly in the Escherichia coli system. However, in our previous study, the yield of MPT64 protein extracellular recovery was still low and plenty of this protein was remain trapped in cytoplasm and periplasm. Recently, nonionic surfactants were efficiently reported to secrete recombinant protein extracellularly. Nonetheless, it must be clarified whether the surfactant supplementation can improve the yield of MPT64 extracellular protein significantly without giving impact on the structure of isolated MPT64 protein and can minimized the cell lysis effect. MPT64 protein secretion was carried out by comparing the effects of surfactants Tween 80 and Triton × 100 at various concentrations. Triton × 100 was able to increase the extracellular MPT64 protein gain up to 3 times higher than Tween 80 and it was in line with the greater level ratio of cell leakage of Triton × 100 compared to that of Tween 80. Similarly, the viable cell of the cultures decreased dramatically. However, both surfactants did not interfere the structure of MPT64 protein. In conclusion, Triton × 100 can be chosen as the supporting surfactant to assist the act of peptide signal in improving the resulting of MPT64 extracellular protein.